Methotrexate efficacy in the treatment of hydatidiform mole - Fernández Molinari, Luis (2015)
Objetive: To determine the efficacy of methotrexate (MTX) in the treatment of hidatidifonte cool. Design: descriptive, comparative study. Material and Methods: rates of recurrence and evolution is compared to choriocarcinoma in hydatidiform mole patients who received treatment with MTX and those not receiving MTX. The sample universe consisted of 166 medical records of patients with histological diagnosis of hydatidiform mole and Bethlehem in Trujillo Regional Hospital, from January 1966 to December 2000, of which 83 patients received MTX and 83 no. He incliyó patients with at least one year post-voidal of cool and excluded patients in whom hysterectomy was performed. Results: 0.6% of patients treated with MTX evolved to recurrent mole and choriocarcinoma no. The patients who received MTX showed a high percentage of choriocarcinoma (4.8%) and recurrent mola (4.2%). A significant association between the administration of MTX and the evolution of molahidatidiforme (p <0.005) was found. Conclusion: The use of prolifiláctico methotrexate in patients with hydatidiform mole decreases the occurrence of recurrent mole and choriocarcinoma.